Appraising the Origins of British Language and the Challenges of Business Communication - Dansou, Bertin Y. (Advances in Social Sciences Research Journal, 2022)
The English language has shown the same history and development as Anglo-Saxon and British peoples. English ancestors were great warriors and business people. They showed great achievements in Germanic, Scandinavian, Greek, Roman ,French ,English and American wars ,and other activities. This makes English a relevant and suitable language for Wars, social and economic activities; hence the sociolinguistic origins and dimensions of English and business. Nevertheless, this well-known and important language is challenged by business demands that shape and reshape English for communication in the direction of modernity and globalization. The purpose of this analysis is to use structuralism criticism to revisit the diachronic and synchronic aspects of the language to demonstrate connections and interconnections between the origins of the language ,its development and the use of business communication for the promotion of social, political and economic activities. Languages promotion and business development or success are then interdependent for sustainable development